Evaluasi Kelayakan Teknis Struktur Gedung Mall Indramayu - Istikomah, Hulfa; Ety Fitriyani (Syntax Literate, 2025)
This study aims to evaluate the technical feasibility of the structure of the Indramayu Mall Building which until now does not have a Certificate of Functional Fitness (SLF). The assessment is carried out through non-destructive methods in the form of Hammer Test, Leeb Hardness Test, and Rebar Scanner to assess concrete strength, material hardness, and reinforcement condition. The test results showed that the building structure met the technical requirements in accordance with SNI 2847:2019 and SNI 07-7178-2006. These findings provide a basis for recommendations for the feasibility of building functions and support the implementation of SLF in accordance with national regulations.